Determinants of COVID-19 vaccine hesitancy among Italian healthcare workers: A cross-sectional study - Cristiana FERRARI; Andrea MAZZA; Claudia SALVI; Andrea MAGRINI; Luca COPPETA (GIornale Italiano di Psicologia e Medicina del Lavoro)
Introduction: As the COVID-19 pandemic spread globally, healthcare systems have been overwhelmed with both direct and indirect mortality from other treatable conditions. Vaccination has been crucial in preventing and eliminating the disease, which is why the development of the SARS-CoV-2 vaccine has been accelerated worldwide. While vaccination is a commonly recognized effective means, according to the World Health Organization (WHO), vaccine hesitancy is a global health problem. This paper aimed to study determinants of COVID-19 vaccine hesitancy in a sample of Italian healthcare workers. Methods: We conducted a cross-sectional online survey of nurses in four Italian regions between 20 and 28 December 2020 to obtain data on the acceptance rate of the forthcoming SARS-CoV-2 vaccination, in order to plan specific interventions to increase vaccination coverage. 531 of the 5,000 nurses invited completed the online questionnaire. Results: The majority of nurses enrolled in the study (73.4%) were female. Of all the nurses, 91.5% intended to accept the vaccination, while 2.3% were against it and 6.2% were undecided. Female gender and confidence in vaccine efficacy were the main predictors of vaccine intention among the study population using a logistic regression model, while other factors including concerns about vaccine safety and concerns about possible side effects were not significant. Discussion and Conclusion: Despite the availability of a safe and effective vaccine, the intention to be vaccinated was suboptimal among nurses in our sample. We also found a significant number of people undecided about whether or not to accept the vaccine. Contrary to expectations, vaccine safety concerns did not affect the acceptance rate. Nurses’ perception of vaccine efficacy and the female gender were the main factors influencing attitudes toward vaccination in our sample. Since the success of the COVID-19 immunization plan and in general of other vaccination plans depends on the acceptance rate, these results are of great interest to public health policies. Interventions aimed at increasing workers’ awareness of the effectiveness of vaccination should be promoted among nurses to increase the number of people vaccinated.